Analisis profesionalitas guru berdasarkan pengalaman mengajar, motivasi berprestasi, dan ketersediaan sarpras - Istinuryanti, Istinuryanti (Piramida Akademi, 2024)
This study aims to determine : 1)how much influence the teaching experience, achievement motivation, availability of infrastructure on the professionalism of elementary school teachers in Paliyan District; 2) how much influence does the teaching experience have on the professionalism of elementary school teachers in Paliyan District; 3) how much influence does achievement motivation have on the professionalism of elementary school teachers in Paliyan District; 4) how much influence does the availability of infrastructure facilities on the professionalism of elementary school teachers in Paliyan District. This research is quantitative approach. The respondents are 176teachers of elementary school teachers in Paliyan Districtwhich spread in twenty elementary schools. The amount sample is 110 teachers determined by proposional random propotional sampling technique. Data are collected using questionnaires. Data analysis includes multiple regression analysis using SPSS 24 which coundcts normality test, , linierity test, and multicolinierity test as the pre requeisite. From the data analysis and some discussions, it is concluded that : 1) The teaching experience, achievement motivation, and availability of infrastructure contribute positively and significantly to the professionalism of the teacher which means having a long teaching experience, strong achievement motivation and the availability of supporting infrastructure, the teacher's professionalism will increase; 2) There is a positive and significant contribution of teaching experience to teacher professionalism, meaning that the longer the teaching experience possessed by the teacher, the more professional the teacher will be; 3) There is a positive and significant contribution of achievement motivation towards teacher professionalism, meaning that the stronger the achievement motivation possessed by the teacher, the more professional the teacher will be; 4) There is a positive and significant contribution to the availability of available infrastructure, so that the professionalism of teachers will increase.